A Differential Scanning Calorimetric Study of Carbide Transition in 10Cr Tempered Martensitic Steels. Issue 1754 (10th June 2015) - Wang, H.C.
ABSTRACT: The process and kinetics of carbide precipitation upon tempering of an Fe-10Cr-0.15C (wt.%) alloy fabricated from high-purity components has been studied. Differential scanning calorimetry reveals three exotherms in a temperature range of 100-700°C. Using advanced electron microscopy and Kissinger analysis, the exothermic processes have been interpreted. Cementite precipitated first upon tempering at temperatures as low as 200°C; M7 C3 and M23 C6 appear at higher temperatures, precipitating at approximately the same time but on different sites (M7 C3 within grains and laths and M23 C6 on grain and lath boundaries). Subsequently, the more stable M23 C6 coarsens at the expense of M7 C3, which dissolves. The first exotherm was interpreted as being related to the precipitation of cementite whilst the other two overlapping exotherms were interpreted as relating to the concurrent precipitation and coarsening of M7 C3 and M23 C6, respectively. In-situ SEM and TEM observation is being conducted in order to obtain a more precise understanding and further validate the interpretation of the DSC results.